The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/10447318.2021.1925437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Presence and Physical Activity on Player Well-being in Augmented Reality Games: A Diary Study

Abstract: In this study, we investigate presence in augmented reality games and how it is related to daily physical activity levels and well-being of players. In a diary study, 49 participants played "Ingress" for 14 days and filled out a questionnaire that consisted of several Likert scales, at the end of every day. Multilevel analyses showed that presence was associated with daily walking duration and daily subjective vitality, and daily walking duration was associated with subjective vitality of players in the same-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…The results of this study are in line with previous studies which explained that Pokemon Go is an augmented game that requires players to travel to various locations in the real world which the distances was relatively far. Thus, after carried out this game, players can increase their PA level to be better than before (Althoff et al, 2016;Chaput & Leblanc, 2017;Ewell et al, 2020;Kosa & Uysal, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with previous studies which explained that Pokemon Go is an augmented game that requires players to travel to various locations in the real world which the distances was relatively far. Thus, after carried out this game, players can increase their PA level to be better than before (Althoff et al, 2016;Chaput & Leblanc, 2017;Ewell et al, 2020;Kosa & Uysal, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They identified immersion as a significant negative predictor of intention to play while walking. Walking while playing was also covered by Kosa et al in their study on presence in AR games and how it is related to daily physical activity levels and the well-being of players [60]. They demonstrated that presence was associated with daily walking duration and daily subjective vitality, suggesting that presence could be an important factor for engagement in AR games.…”
Section: Ar Games Activity and Social Presencementioning
confidence: 95%
“…Jin, 2021 [59] "AR Journey" Compares the natural user interface and graphical user interface and their impact on users' presence Kosa, 2022 [60] "Ingress"…”
Section: Reference Ar Game Game Type Main Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Kosa and Uysal (2021) used an augmented reality game to test the Effects of Presence and Physical Activity on Player Well-being [32] and found that their method was positively correlated with well-being, but their game design needs more of a social presence element.…”
Section: Limitations and Future Workmentioning
confidence: 99%